2022
DOI: 10.1007/s10787-022-00931-1
|View full text |Cite
|
Sign up to set email alerts
|

Natural compounds as safe therapeutic options for ulcerative colitis

Abstract: Ulcerative colitis (UC) is a chronic inflammatory bowel disease of unknown etiology. Several conventional treatments for UC such as corticosteroids, immunosuppressive agents, tumor necrosis factor antagonist, integrin blockers, and interleukin antagonist, and salicylates are available but are associated with the various limitations and side-effects. None of the above treatments helps to achieve the ultimate goal of the therapy, i.e., maintenance of remission in the long-term. Natural remedies for the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 159 publications
0
14
0
Order By: Relevance
“… 1 According to the World Health Organization (WHO), the prevalence of UC is about 250 per 100,000, affecting both sexes equally and any age. 2 Worldwide, IBDs cause essential morbidity and heavy productivity losses, and as a result of the increasing rate of incidence and prevalence of IBDs and the lack of a cure or effective long-term treatment options, there is a substantial financial burden to the healthcare systems. 3 …”
Section: Introductionmentioning
confidence: 99%
“… 1 According to the World Health Organization (WHO), the prevalence of UC is about 250 per 100,000, affecting both sexes equally and any age. 2 Worldwide, IBDs cause essential morbidity and heavy productivity losses, and as a result of the increasing rate of incidence and prevalence of IBDs and the lack of a cure or effective long-term treatment options, there is a substantial financial burden to the healthcare systems. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, some traditional herbal drugs and natural remedies have shown satisfactory efficacy and comparatively fewer side effects in UC treatment. , The dried roots of Pulsatilla chinensis (Bunge) Regel, has been used in traditional Chinese medicine to treat intestinal amebiasis, dysentery, and enteritis. , Triterpenoid saponins are considered the main active constituents in P. chinensis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, components of natural compounds have been widely studied because of their multitarget, multipathway, and multieffects on UC. , Among them, Rhein (RH), the active ingredient from Rheum palmatum L., Polygonum multiflorum Thunb, and Cassia tora L., among others, has various positive pharmacological activities, including those relating to anti-inflammation, antioxidation, and the regulation of intestinal flora. Based on our preliminary research and previous relevant experimental research, RH has been shown to have multiple therapeutic effects on UC .…”
Section: Introductionmentioning
confidence: 99%